2015
DOI: 10.1371/journal.pone.0125640
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Sequence of Isocaloric Meals with Different Protein Contents on Plasma Biochemical Indexes in Pigs

Abstract: Nutrient composition and pattern of food intake may play a significant role in weight gain. The aim of this study was to document the effects of a daily 3-meal pattern with isocaloric diets containing different dietary protein contents on growth performance and different plasma biochemical indexes including amino acid plasma concentration in castrated male pigs. Then, 21 DLY (Duroc×Landrace×Yorkshire) pigs aged 60 days were assigned randomly into 3 groups: a control group (crude protein, CP 18.1%), a group rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 46 publications
0
10
1
Order By: Relevance
“…Nutritional requirements change dynamically during the day and vary also among animals, even in age‐ or sex‐homogeneous populations . Previous studies have indicated that nutrient efficiency could be improved by better adjusting nutrient supplementation to individual requirements of the animals . This study differs from previous ones since the level of dietary protein was given in a different time‐scale during the day in a context of similar nutritional conditions between the experimental groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nutritional requirements change dynamically during the day and vary also among animals, even in age‐ or sex‐homogeneous populations . Previous studies have indicated that nutrient efficiency could be improved by better adjusting nutrient supplementation to individual requirements of the animals . This study differs from previous ones since the level of dietary protein was given in a different time‐scale during the day in a context of similar nutritional conditions between the experimental groups.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the daily three‐meal pattern with different dietary protein contents, based on the circadian clock for weight management, body weight regulation, hunger control, and metabolic disease management, is not supported by sufficient evidence in the associated scientific literature. In our previous study, we found that the sequence and quantity of alimentary protein intake affected the insulin/glucagon ratio, as well as amino acid concentrations including branched chain amino acids, methionine and serine . It is then conceivable that meal pattern with pigs receiving high then basal and then low crude protein meals daily may help to improve the weight gain of growing pigs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that a high protein meal in the evening significantly increased the plasma branched-chain amino acid (BCAA) concentration on the next morning, even more than 12 h after the meal, demonstrating that varying the protein content in the meal pattern with different dietary protein contents may affect the use of some essential amino acids ( Nishioka et al., 2013 ). Our previous study also found that the sequence and quantity of alimentary protein intake affect the insulin/glucagon ratio, as well as amino acid concentrations including BCAA, methionine and serine ( Xie et al., 2015 ). Strong associations exist among the important indexes, ADG, ADFI, and F/G, all of which reflect growth and development in pigs.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have reported that feeding time affects body weight and the risk of obesity in humans 7 , 8 . Our previous study showed that a daily meal sequence with different dietary crude protein (CP) affected the metabolism and growth performance in growing pigs 9 , and improved muscle quality characteristics 10 . As one of the most important parts of milk, fat or fatty acid is important for offspring growth 11 .…”
Section: Introductionmentioning
confidence: 99%